Assessment of serum dipeptidyl peptidase-IV levels in autoimmune thyroid disease. Issue 7 (July 2022) - Zhang, Yuanyuan; Fu, Ying; Yang, Yuxian; Ke, Jing; Zhao, Dong
Objective: Decreased serum dipeptidyl peptidase-IV (sDPPIV) levels have been reported in patients with autoimmune diseases. However, few studies have analyzed the association between sDPPIV levels and autoimmune thyroid disease (AITD). This study aimed to evaluate the association between sDPPIV levels and three types of AITD: Graves' disease (GD), Graves' ophthalmopathy (GO), and Hashimoto's thyroiditis (HT). Methods: Patients newly diagnosed with GD (n = 65), GO (n = 22), and HT (n = 27) and healthy individuals (n = 30) were recruited. Clinical characteristics and thyroid function data were collected. sDPPIV was measured using enzyme-linked immunosorbent assays. Results: Compared with controls (786.3 ± 46.95), patients with GD and GO had significantly lower sDPPIV levels (662.2 ± 38.81 and 438.4 ± 31.78). Additionally, sDPPIV levels were negatively associated with antithyroid peroxidase antibody (r = −0.20) and antithyroglobulin antibody (r = −0.19), but there was no significant relationship between thyroid hormone and sDPPIV levels. GO cases were divided by proptosis with and without muscle thickening; sDPPIV levels were lower in the muscle thickening group than those in the without muscle thickening group. Logistic regression analysis showed that sDPPIV was negatively correlated with GO and GD. Conclusions: sDPPIV concentrations were abnormal in patients with GD and GO, and reduced sDPPIV expression may be involved in the progression of GO and GD.